(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Cancellation of elective operations is a noteable dilemma in many hospitals. Late cancellation of operation affect not only hospital resources but causes emotional disturbance in patients as well. Objective: To find out the incidence and causes for late cancellation of elective operations. Study Design: It is a prospective observational study. Method and material: This prospective observational, hospital based study was conducted in one of the surgical department of Sir Ganga Ram Hospital Lahore for a period of one year from 2nd Jan, 2015 to 3rd Jan 2016.Data was collected of all the patients whose operations were cancelled on intended day of operation and reasons for cancellation were noted on specially designed proforma. Result: A total of 1440 pts were operated on elective operation list. Eighty four cases were postponed. Cancellation rate was found to be 5.8% mostly due to medical reason (41.7%), followed by shortage of time (25%),blood not arranged (9.5%), strikes (7.1%), administrative reason(6%,) patient restrain (6%), patient not prepared (3.6%) and change of p